Accidental Neoliberalism and the Performance of Management: Hierarchies in Export Agriculture on the Zimbabwean-South African Border. Issue 4 (2nd April 2016) - Bolt, Maxim
Abstract: South Africa's export farms have shifted from racialised paternalism to corporate managerialism. But how have workforce dynamics changed? This article offers an ethnographic perspective on agriculture on the transient Zimbabwean border. An 'actor-centred' approach examines the causes and extent of transformation. Who furthers managerial logics? Why? With what effects? White farmers emphasise impersonal, rationalised business for diverse reasons. What looks like part of a single global process of neoliberalisation is an accidental result. At the same time, foreign supermarket-funded development projects become subjected to logics of workforce paternalism. Managerialism itself has limited effect on labour arrangements. Workers' hierarchies and cross-border networks are built on different principles from global supply chains. From within each network, it is as if the other were invisible.